THE ETHNO MEDICINAL SURVEY AND EVALUATION OF TWO RECIPES USED IN MANAGING SICKLE CELL DISEASE IN ILE-IFE COMMUNITY OF OSUN-STATE, NIGERIA.: Ethnomedicinal survey - Cyril-Olutayo, Mojisola Christianah; Ajayi, Dorcas O; Odunowo, Olayinka O (African Journal of Traditional, Complementary and Alternative Medicines, 2023)
Background: Ethno-medicinal survey of herbal recipes used in managing sickle cell disease in Ile-Ife, Osun-State, Nigeria was carried out and two recipes selected for antisickling studies. Materials and Methods: Information was obtained using semi-structured questionnaires and open interview from respondents consisting of herb sellers, traditional medical practitioners, artisans and traders in two local government areas of Ife. Two recipes from the survey were selected for antisickling studies. Aqueous extract of each recipe was obtained by boiling the constituents in water for 1 h while the hydro ethanolic extracts were obtained by maceration in 70% ethanol for 72 h. Inhibitory and reversal antisickling properties were assessed using sodium metabisulphite as deoxygenating agent, vanillic acid (inhibitory agent), para-hydroxybenzoic (reversal agent) acid as positive controls while phosphate buffered saline was employed as negative control. Results: Fifty four recipes comprising forty six plants were obtained from the ethno-medicinal survey. The respondents comprised of 44% men and 56% women. The most frequently and commonly used plants belong to family Fabaceae. The inhibitory and reversal activities of the aqueous extract of recipe 1 (81.37± 1.09%, 88.56 ±1.38% respectively) were significantly (p < 0.05) higher than recipe 2 (78.51 ± 0.78% inhibition and 79.8 ± 2.16% reversal) at same concentration. The hydro-alcoholic extracts of recipes 1 and 2 gave highest inhibitory activities at 0.5 mg/mL (69.25 ±1.30% and 68.28 ±2.78% respectively). Conclusion: This study documented the medicinal plants and recipes used in Ile-Ife for managing sickle cell disease, and validated the ethno-medicinal claim of two recipes.